Strategi Pengembangan Pariwisata Berkelanjutan di Desa Sukamukti: Pendekatan Analisis SWOT dan Analisis PEST - Priani, Zalsa Az Zahra; Dienaputra, Reiza D.; Ucu Rakhman, Cecep (Sekolah Vokasi, Universitas Gadjah Mada, 2025)
This study aims to identify the natural tourism potential in Sukamukti Village, Maniis District, Purwakarta Regency, and formulate sustainable tourism development strategies using SWOT and PEST analysis approaches. A qualitative descriptive methodology was employed, involving direct observations and interviews with key stakeholders, including the village head, the Sukamukti Tourism Awareness Group (Pokdarwis), local residents, and subdistrict officials. The SWOT analysis identified internal factors (strengths and weaknesses) and external factors (opportunities and threats) to develop strategic solutions, while the PEST analysis assessed the political, economic, social, and technological influences affecting tourism development. The study emphasizes the importance of integrating internal capabilities with external dynamics to formulate adaptive and sustainable strategies. The findings offer valuable insights for local stakeholders and policymakers to enhance tourism development in alignment with the community’s needs and socio-economic conditions